Narrating the Transgressive Self. (November 2014) - Goode, Erich
Since Augustine penned his Confessions, authors of memoirs describing their transgressive behavior have teetered on a balance beam between telling an interesting, exciting, naughty story, and exculpating their character for their participation in it, through the use of deviance neutralizing devices; here sociologist Erich Goode explains how this balancing act is accomplished.